Construction of Femininity of the Main Characters in Pride and Prejudice (2005) and Pride and Prejudice and Zombies (2016) - Soleha, Annisa Husna; Meiutia, Faridah; Bayhaqi, Muhammad Nabil; Maiza, Thiska Septa (CV. ITTC INDONESIA, 2025)
This research examines the portrayal of feminists in Pride and Prejudice (2005) and Pride and Prejudice and Zombies (2016). Using a qualitative descriptive approach, this study analyzes how the main female characters, Elizabeth Bennet and Jane Bennet, exemplify feminist principles. The study presents three key findings. First, it reveals that both Elizabeth and Jane view marriage as based on love and happiness rather than social or economic status. Second, Elizabeth's character is portrayed as an independent woman with critical thinking skills, shown through her efforts to defend her honor and her family's reputation. Lastly, the inclusion of zombie elements in Pride and Prejudice and Zombies highlights the two female characters as brave, strong women who do not rely on men, demonstrated by their ability to take care of themselves and those around them.